Discrete-element modelling of rock communition in a cone crusher using a bonded particle model. Issue 2 (29th April 2014) - Lowndes, I.; Li, H.; McDowell, G.
Abstract : It is known that discrete-element method (DEM) modelling of rock size reduction can be achieved using two approaches – the population balance model (PBM) and the bonded particle model (BPM). However, only the PBM has been successfully used in DEM modelling of a cone crusher in the literature. The aim of this paper is to explore the feasibility of using the BPM to represent the size reduction of rock experienced within a cone crusher chamber. The feed rock particles were represented by isotropic dense random packing agglomerates. The simulation results were compared with the PBM simulation results and it was shown that the BPM cone crusher model was able to satisfactorily replicate the performance of a cone crusher and can provide a more accurate prediction of the percentage of fine products. In addition, the novel contribution of this work is that the rock feed material comprised particles of realistic shapes that break into more realistically shaped fragments compared with the fragments with defined shapes in the PBM.